2020
DOI: 10.1177/2050312120942118
|View full text |Cite
|
Sign up to set email alerts
|

Interactive patient education via an audience response system in cardiac rehabilitation

Abstract: Objectives: Patient education and compliance play an important role in the success of rehabilitation in cardiovascular diseases. The aim of this study is to analyze whether interactive learning methods, in this study, the audience response system with a “clicker,” can improve the learning success of patients during and after their rehabilitation process. Methods: In a randomized, prospective cohort study, a total of 260 patients were randomized to either an interactive training group using Athens audience resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
1
0
5
Order By: Relevance
“…The following inclusion criteria were established as requirements to participate in the studies: Voluntary participation of candidates for coronary angioplasty treatments: patients with ischemic coronary disease; and patients requiring rehabilitation programs, although not necessarily hospitalized. It was found that six studies (32,33,36,39,40,41) were developed in the Telemedicine modality, resorting to voice calls, text messages, own software programs and digital platforms for synchronous and asynchronous meetings. As for the participants' allocation to the intervention or control groups, they were randomly assigned by professionals that would not develop any intervention directly with the participants.…”
Section: Resultsmentioning
confidence: 99%
“…The following inclusion criteria were established as requirements to participate in the studies: Voluntary participation of candidates for coronary angioplasty treatments: patients with ischemic coronary disease; and patients requiring rehabilitation programs, although not necessarily hospitalized. It was found that six studies (32,33,36,39,40,41) were developed in the Telemedicine modality, resorting to voice calls, text messages, own software programs and digital platforms for synchronous and asynchronous meetings. As for the participants' allocation to the intervention or control groups, they were randomly assigned by professionals that would not develop any intervention directly with the participants.…”
Section: Resultsmentioning
confidence: 99%
“…O desenvolvimento e a implementação de tecnologias educacionais podem efetivamente prevenir e reduzir as taxas de morbimortalidade por doenças cardiovasculares, em prol de mudanças comportamentais, pois visam aumentar o conhecimento das pessoas sobre os fatores de risco das doenças crônicas, gerando empoderamento para as mudanças no estilo de vida e, portanto, podem prevenir o desenvolvimento da doença e seus agravos e influenciar na procura de tratamento quando a doença já está instalada (STOEVESANDT et al, 2020).…”
Section: Métodosunclassified
“…O envolvimento das equipes de saúde no fluxo de atendimento dessa clientela precisa ser coeso, harmonioso e interativo 20 . O paciente estará na ponta da assistência, é a ele que se direciona e se destina essa assistência.…”
Section: ) the Impact Of Drug Related Problems On Health-related Qual...unclassified
“…O paciente estará na ponta da assistência, é a ele que se direciona e se destina essa assistência. A educação em saúde e a sua adesão, demostrada em comportamentos saudáveis no estilo de vida, na prática diária do seu autocuidado vão se constituir no êxito, no sucesso da reabilitação ou do controle das doenças cardiovasculares 20,21 .…”
Section: ) the Impact Of Drug Related Problems On Health-related Qual...unclassified
See 1 more Smart Citation